The wisdom and foolishness of God : First Corinthians 1-2 in theological exploration - Chalamet, Christophe; Askani, Hans-Christoph (Minnepolis Fortress Press, 2015)
The first two chapters of Paul's first epistle to the Christians of Corinth, written in the fifth decade of the first century, have played a significant role in the history of Christian theology. Interpreting the central event in Christianity, namely the crucifixion of Jesus, Paul reflects on the wisdom and foolishness of God, which he opposes to the world's wisdom. According to Paul, the "word of the cross," which is "foolishness" to some and "scandal" to others, leads to an upheaval in one's way of thinking. For two millennia, theology has often turned to these passages in order to sustain its reflection. Many central questions emerge from Paul's text on the meaning of a crucified Messiah, on God's omnipotence, weakness, and suffering. This volume hopes to achieve two things by seeking to place exegetes, historians, philosophers, and theologians in conversation: to better understand Paul's text and its reception and also to examine the ways in which it can nourish our theological reflection today.
Introduction -- 1. Crucifixion as wisdom : exploring the ideology of a disreputable social movement / John M.G. Barclay -- 2. The weakness of God : a radical theology of the cross / John D. Caputo -- 3. On a road not taken : iterations of an Alexandrian Paul / Kellen Plaxco -- 4. Maximus the Confessor on the foolishness of God and the play of the word / Andrew Louth -- 5. Paul's refusal of wisdom in Aquinas's commentary on 1 Corinthians : notes on philosophy in the Summa of theology / Adam Eitel -- 6. Election and providence in the theology of Thomas Aquinas : reading the Summa in light of his commentary of 1 Corinthians 1-2 / Michael T. Dempsey -- 7. Luther's theologica paradoxa in Erasmus and Cusanus / Gnter Bader -- 8. The cross of wisdom : ambiguities in turning down apologetics (Paul, Anselm, Barth) / Anthony Feneuil -- 9. The wisdom in God's foolishness : Karl Barth's exegesis of 1 Corinthians 1-2 / Andrew R. Hay -- 10. The word of the cross in the conflict of interpretive power : on the genealogy of theology deriving from the spirit of Pauline rhetoric / Philipp Stoellger -- 11. On justification and beyond -- an attempt / Matthias D. Wthrich -- 12. The foolishness and wisdom of all God's ways : the case of creation ex nihilo / Kathryn Tanner -- 13. Witnessing to the cross, forgetting human sin : a systematic-theological inquiry in the "word of the cross" (1 Cor. 1:18) / Henning Theissen -- 14. The cross of Christ and God's power / Marc Vial -- 15. God's weakness and power / Christophe Chalamet -- 16. The paradox of faith / Hans-Christoph Askani -- 17. "To know nothing except Jesus Christ, and him crucified" : supralapsarian Christology and a theology of the cross / Edwin Chr. van Driel.
"Papers presented at an international theological conference held May 23-25, 2013, at the University of Geneva and organized by the Facult de thologie protestante and the Institut romand de systmatique et d'thique (IRSE) of that University"--Page xi.
Includes bibliographical references and index.
Keywords: Paul, -- the Apostle, Saint; Bible. -- Criticism, interpretation, etc; God (Christianity) -- History of doctrines -- Early church, ca. 30-600.